2018
DOI: 10.1158/0008-5472.can-17-1366
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–Stroma IL1β-IRAK4 Feedforward Circuitry Drives Tumor Fibrosis, Chemoresistance, and Poor Prognosis in Pancreatic Cancer

Abstract: Targeting the desmoplastic stroma of pancreatic ductal adenocarcinoma (PDAC) holds promise to augment the effect of chemotherapy, but success in the clinic has thus far been limited. Preclinical mouse models suggest that near-depletion of cancer-associated fibroblasts (CAF) carries a risk of accelerating PDAC progression, underscoring the need to concurrently target key signaling mechanisms that drive the malignant attributes of both CAF and PDAC cells. We previously reported that inhibition of IL1 receptor-as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 48 publications
6
126
1
1
Order By: Relevance
“…We previously demonstrated that IL1/JAK/STAT signaling is the key pathway responsible for iCAF formation in PDA (Biffi et al, 2019). While a basal level of IL1 is expressed in PDA tumor cells that lack TP63 expression (Tjomsland et al, 2011;Zhang et al, 2018), a key finding in our current study is in demonstrating that a remarkable heterogeneity exists in IL1 expression in the human disease, with the highest levels being found in TP63-expressing squamous subtype tumors.…”
Section: Discussionmentioning
confidence: 46%
“…We previously demonstrated that IL1/JAK/STAT signaling is the key pathway responsible for iCAF formation in PDA (Biffi et al, 2019). While a basal level of IL1 is expressed in PDA tumor cells that lack TP63 expression (Tjomsland et al, 2011;Zhang et al, 2018), a key finding in our current study is in demonstrating that a remarkable heterogeneity exists in IL1 expression in the human disease, with the highest levels being found in TP63-expressing squamous subtype tumors.…”
Section: Discussionmentioning
confidence: 46%
“…NFE2L2 encodes for Nrf2, which is a key regulator of antioxidant machinery and favors pancreatic cancer growth and progression . Similarly, cytokines including IL‐1b , IL‐6 and IL‐8 are implicated in tumorigenesis and their increased expression is associated with the development, progression and therapeutic resistance in pancreatic cancer . The role of SERPINB2 , which encodes the plasminogen activator inhibitor 2, is context‐dependent in cancer and both tumor‐suppressing and promoting functions are reported .…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, cytokines including IL-1b, IL-6 and IL-8 are implicated in tumorigenesis and their increased expression is associated with the development, progression and therapeutic resistance in pancreatic cancer. [30][31][32][33][34][35] The role of SERPINB2, which encodes the plasminogen activator inhibitor 2, is contextdependent in cancer and both tumor-suppressing and promoting functions are reported. 36,37 However, a potential tumorsuppressive role of SERPINB2 is earlier described in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Via matrix synthesis and remodeling, they can modulate ECM stiffness and hypoxia facilitating tumor cells mobility and invasion. Through secreted molecules, such as growth factors, cytokines, chemokines and microRNAs (miRNAs), CAFs support tumor growth and induce resistance to therapy (Karagiannis et al, 2010;Zhang et al, 2018). Moreover, a direct cell-to-cell contact between CAFs and cancer cells, mediated by N-cadherin/E-cadherin adhesion complex, has been recently proved to promote tumor invasion (Labernadie et al, 2017).…”
Section: Co-cultures With Cafsmentioning
confidence: 99%